An examination of sex differences in neurocognition and social cognition in first-episode psychosis. (January 2018) - Danaher, Haylee; Allott, Kelly; Killackey, Eóin; Hester, Robert; Cotton, Sue
Abstract: Due to the dearth and conflicting findings of previous research, it is unclear whether males and females with first-episode psychosis (FEP) differ in their neurocognitive and social cognitive abilities. The aims of the current study were to investigate whether: (i) there are sex differences in neurocognition and social cognition among young people with FEP; and (ii) they resemble those observed in age-matched healthy controls. The current study involved secondary analysis of data from a previous study in which a large neurocognitive and social cognitive battery was administered to 146 individuals with FEP and 46 healthy controls aged 15–25 years. Seven two-way between-groups multivariate analysis of variances revealed that FEP participants were impaired relative to controls on all cognitive domains. Only one main effect of sex was found with males, regardless of group, outperforming females on verbal comprehension. A significant interaction effect was found for information processing speed with FEP females outperforming FEP males on the Symbol Digit Modalities Test; however, post-hoc analysis of the mean difference was not significant. Despite few sex differences, the current study highlights that cognitive impairment is a key feature of FEP that should be a treatment target in early intervention. Highlights: Cognitive deficits were found in first-episode psychosis versus controls. No sex differences in neurocognition or social cognition found among those with FEP. Regardless of group, males outperformed females on verbal comprehension. Cognitive impairment should be a treatment target in early psychosis.